Estimación de los promedios diarios y mensuales de la radiación difusa sobre un plano horizontal en Alajuela, Costa Rica - Wright Gilmore, Jaime (1988)
Separating the global radiation on a horizontal Surface into direct and diffuse components is required in the simulation of solar energy systems. Many models have been developed for this purpose. The aim of this study is to establish, from the data collected over the period 1983-1985 in Alajuela, Costa Rica, monthly mean daily correlations between: (a)diffuse fraction and clearness index; (b) diffuse fraction and fractional sunshine duration. Comparison with the most commonly use equation, Page´s correlation, gives good agreement for daily monthly average of the relationship between diffuse fraction and  clearness index. A correlation connecting monthly mean daily diffuse radiation together with the clearness index and percent possible sunshine is found to be most accurate one for Alajuela, Costa Rica.